A taxonomic revision of the South American genus Discolobium (Leguminosae, Papilionoideae) - Sartori, Ângela Lúcia Bagnatori; Neves, Ianny Marques; Seleme, Elidiene Priscila; Mansano, Vidal De Freitas (Phytotaxa, 2017)
Discolobium, an exclusively South American legume genus, includes six species. The nomenclature of each taxon has been reviewed, and six synonyms are presented. Discolobium hirtum, D. junceum, D. leptophyllum, D. psoraleaefolium, D. pulchellum and D. tocantinum can be differentiated mainly by the number and shape of leaflets, degree of fusion of calyx lacinia, morphology of calyx lacinia, petal and fruit wings, and ornamentation of the seed chamber. Species of this genus occur in Pantanal, Chaco, and Caatinga vegetation associated with marshes and river banks and in tropical ombrophilous alluvial forests, either dry or flooded most of the year. An identification key to the species is presented, together with a detailed taxonomic revision of the genus and its species, distribution maps, linedrawings, and comments on the taxonomy and ecology of each species. Lectotypes for D. elongatum, D. hirtum, D. junceum, D. leptophyllum, D. leptophyllum var. junceum, D. leptophyllum var. junceum f. grandiflora, D. leptophyllum var. junceum f. parviflora, D. paucijugum, D. psoraleaefolium, D. pulchellum, D. pulchellum var. major, D. pulchellum var. viscosissimum and D. tocantinum are herein designated.